Pengaruh Manajerial Kepala Sekolah dan Motivasi Kerja Terhadap Kinerja Guru SMA di Rayon 3 OKU Selatan - Etika Septiyana; Tri Widayatsih; Mahasir Mahasir (Journal on Education, 2023)
This study was conducted to analyze and describe the influence of principal managerial and teacher work motivation on teacher performance, especially in high school in Region 3 OKU Selatan. The implementation of this research refers to quantitative research methods, with data collection techniques through questionnaires and documentation. To analyze the data, it is done by means of parametric statistical analysis through the t test and F test. The data obtained is carried out by analyzing the prerequisites that have been met such as the normality of the data distribution, and the absence of heteroscedasticity symptoms. The results achieved from this study are partially managerial principals have a significant influence on teacher performance; work motivation has a significant effect on teacher performance; Simultaneously, the principal managerial variables and teacher work motivation proved to have a positive and significant influence on the performance of high school teachers in Region 3 OKU Selatan.